PERFORMANCE ASSESSMENT OF THE PUBLIC AUTHORITIES AND GOVERNANCE BODIES IN RUSSIA - Irina Valeryevna Gersonskaya (Science and Innovation Center Publishing House, 2020)
The article analyzes the main performance indicators of the public authorities and governance bodies in Russia as well as reveals significant problems inherent in the Russian system of public administration.